Content and Language Integration in Academic Reading: Fostering EFL Learners’ Comprehension and Critical Thinking - Asrul Asrul; Abdulhalim Daud; Awaludin Rizal; Suratman Dahlan; Ridayani Ridayani (PT. Global Research Collaboration, 2026)
The study investigates how this integration affects comprehension, critical thinking, student engagement, learner autonomy, and the particular difficulties that students face using thematic analysis. Student perspectives, classroom observations, and classroom records were used to collect data. Using detailed information from ten informants with a range of skill levels, this qualitative case study examines the impact of combining language and content in academic reading for English as a Foreign Language (EFL) learners in higher education. The results show that students' reading comprehension is much improved by contextualizing reading materials, structuring instruction, and connecting the subject to real-world scenarios. Giving students the chance to relate academic material to their own experiences increases their engagement and sense of autonomy. However, issues with technical jargon, a lack of prior knowledge, and the interpretation of statistical or graphical data remain obstacles. Scaffolded analysis, modeling of reading strategies, and pre-teaching of specialist terminology are among the effective tactics identified. These findings highlight the importance of adaptable, targeted teaching strategies for EFL students. Such interventions are essential for fostering critical thinking, academic literacy, and independence. Integrating language and content supports EFL learners in overcoming reading challenges and achieving academic success.